2018
DOI: 10.1177/0954406218781402
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive stiffness control of passivity-based biped robot on compliant ground using double deep Q network

Abstract: Passive dynamic walking exhibits human-like and energy-efficient gait. Biologically inspired compliance introduced to flexible passivity-based robot would be helpful to generate stable locomotion. However, designing adaptive controller for flexible biped on compliant ground still remains a challenge. This paper aims to design an adaptive and model-free stiffness controller for passivity-based flexible biped on compliant ground, where the hip stiffness is modulated by double deep Q network. One benefit of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…After training process, the trained DQN networks would be used as hip impulse torque controller. Combined with the hip stiffness modulation, the biped robot was controlled under proposed controller as equation (31). To evaluate the performance of proposed chaotic controller, four experimental tests were conducted as follows.…”
Section: Controller Setup and Training Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After training process, the trained DQN networks would be used as hip impulse torque controller. Combined with the hip stiffness modulation, the biped robot was controlled under proposed controller as equation (31). To evaluate the performance of proposed chaotic controller, four experimental tests were conducted as follows.…”
Section: Controller Setup and Training Resultsmentioning
confidence: 99%
“…30 Besides, adaptive model-free controllers using RL were proposed to stabilize PDW-based robots, improving robustness to disturbance and time varying environments, while maintain PDW's merits of human-like motion and high energy efficiency. 31,32 So this paper expanded out previous work to improve the PDWbased robot's versatility by stabilizing its chaotic behaviors.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some of the recent optimization approaches for controlling robot locomotion were designed to respond adaptively to environmental changes, unknown initial conditions, and/or damage. Examples include stiffness control of a simulated model of a passive bipedal robot using a double-deep Q network presented in ( Wu et al., 2019 ) and intelligent trial and error algorithm for robots to adapt to damage presented in ( Cully et al., 2015 ). Both algorithms require offline training.…”
Section: Related Workmentioning
confidence: 99%
“…Previous research in legged systems has indicated that leg stiffness is crucial for enhancing versatility over compliant terrains, as well as regulating external disturbances and improving energy efficiency [13][14][15][16]. Furthermore, research in biomechanics has shown that humans and birds adjust leg stiffness based on ground stiffness [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%